Prebiotic evaluation of red seaweed (Kappaphycus alvarezii) using in vitro colon model - Bajury, Dayang Marshitah; Rawi, Muhamad Hanif; Sazali, Iqbal Hakim; Abdullah, Aminah; Sarbini, Shahrul Razid (Taylor & Francis, 2017)
Red seaweed (Kappaphycus alvarezii) cultivated from Sabah (RSS) and Langkawi (RSL) were digested using in vitro mouth, gastric and duodenal model. The digested seaweed then fermented in a pH-controlled batch culture system inoculated with human faeces to mimic the distal colon. Bacterial enumeration were monitored using fluorescent in situ hybridisation, and the fermentation end products, the short chain fatty acids (SCFA), were analysed using HPLC. Both RSS and RSL showed significant increase of Bifidobacterium sp.; from log10 7.96 at 0 h to log10 8.72 at 24 h, and from log10 7.96 at 0 h to log10 8.60 at 24 h, respectively, and shows no significant difference when compared to the Bifidobacterium sp. count at 24 h of inulin fermentation. Both seaweeds also showed significant increase in total SCFA production, particularly acetate and propionate. Overall, this data suggested that K. alvarezii might have the potential as a prebiotic ingredient.